Racism and Cultural Diversity : Cultivating Racial Harmony through Counselling, Group Analysis, and Psychotherapy. - Maher, Maher (Karnac Books, 2011)
M.J. Maher writes for all those interested in the dynamics of racism, from professionals in counselling, group analysis and psychotherapy working in multiracial and multicultural societies to those exposed to racism who need help in dealing with the impact of their experiences. She also addresses the concept of victims becoming perpetrators if support is not given to contain the process. Herself a group analyst, the author experienced at first hand racial discrimination within the system, but rather than succumb has instead produced an enduring and proficient work that draws heavily on personal.